Diffuse Midline Glioma With Osseous Metastases at Diagnosis: A Case Report. Issue 7 (October 2020) - Bhatt, Neel S.; Houser, Kerri; Belongia, Meghan; Ellison, David W.; Foy, Andrew; Jarzembowski, Jason; Kelly, Teresa; Maheshwari, Mohit; Suchi, Mariko; Knipstein, Jeffrey
Abstract : Extraneural metastasis is extremely rare in pediatric patients with high-grade glioma and carries a grim prognosis. Detection of metastases at initial presentation is even rarer. A 15-year-old adolescent girl presented with paraplegia, urinary retention, and a constellation of systemic symptoms. Imaging showed a fourth ventricular lesion, innumerable intradural lesions, leptomeningeal seeding throughout the neuraxis, and numerous osteoblastic lesions involving the spine, ribs, sternum, pelvis, humerus, and femurs. Pathology confirmed metastatic diffuse midline glioma, H3K27M-mutant. Our patient died 2 weeks after initial presentation. Further work is needed to develop effective treatment strategies for these high-risk patients.